The influence of enthusiasm learn and way of learning to result learn class student economics of XI IPS - ade rahmawati; gunawan sudarmanto; nurdin nurdin (JEE (Jurnal Edukasi Ekobis), 2013)
This research aim to know influence of enthusiasm learn and way of learning to result learn class student economics. Method the used is descriptive research of verifikatif with approach of ex post facto and of survey. The result  of research for use: 1). There is influence of enthusiasm learn to result learn class student economics of XI IPS SMA Bina Mulya Bandar Lampung School Year 2012/2013. 2). There is influence of is way of learning to result learn class student economics of XI IPS SMA Bina Mulya Bandar Lampung School Year 2012/2013. 3). There is influence of enthusiasm and way of learning to result learn class student economics of XI IPS SMA Bina Mulya Bandar Lampunh School Year 2012/2013. Key word: enthusiasm learn, way of learning and result learn.